FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU TIDAK AMAN PADA PEKERJA LABORATORIUM GIGI TIRUAN PT IVOGRATIA TEKNOLOGI INDONESIA - Muhammad Naufal Rasyid; Munaya Fauziah (PT. Hasba Edukasi Mandiri, 2025)
Occupational safety and health (OSH) in dental prosthetics laboratories are crucial in reducing the risks of accidents and health disturbances due to exposure to harmful substances. This study aims to determine the factors related to unsafe behavior among workers in the dental prosthetics laboratory at PT Ivogratia Teknologi Indonesia. This research uses a quantitative design with an analytic approach and data collection through questionnaires. The population used is all active workers in the laboratory, with a sample of 60 people. The results show that age, gender, and education level have a significant relationship with unsafe behavior. Younger workers and those with lower education levels tend to show unsafe behavior. These findings are expected to contribute to efforts to improve workplace safety in dental prosthetics laboratories through approaches that are more responsive to worker characteristics.